Variations in carbon isotopic composition of fatty acids in Arctic pelagic particulate organic matter: a preliminary assessment over a latitudinal gradient - Kohlbach, Doreen; Guillou, Gaёl; Wold, Anette; Hop, Haakon; Graeve, Martin; Assmy, Philipp; Lebreton, Benoit (Frontiers in Marine Science, 2025)
Studies of Arctic food-web structure and function by means of carbon isotopic composition (δ13C) of fatty acids (FAs) have a main challenge of identifying a proper baseline for pelagic particulate organic matter (PPOM). To assess variations in δ13C values of the FAs 16:1(n-7), 20:5(n-3) and 22:6(n-3) in PPOM, seawater was collected along a latitudinal sea-ice gradient across the Barents Sea in August 2019, spanning ice-free to fully ice-covered stations. δ13C values varied strongly along the sampling transect in all three FAs (16:1(n-7): -32.2 to -28.9 ‰, 20:5(n-3): -37.4 to -29.8 ‰, 22:6(n-3): -34.7 to -29.3 ‰) and, independently of the FA, were consistently higher at ice-covered (δ13C: -30.2 ± 1.1 ‰) vs. ice-free stations (δ13C: -33.8 ± 2.2 ‰). This was likely the result of the contribution of ice-associated algae to PPOM due to ice melt as ice algae often have higher δ13C values than pelagic algae. Latitudinal differences in δ13C values of 20:5(n-3) and 22:6(n-3) displayed a similar trend, which partly differed from 16:1(n-7). This was likely related to differences in FA synthesis pathways and cellular functions between the membrane-associated FAs 20:5(n-3) and 22:6(n-3) and the storage FA 16:1(n-7). The δ13C values presented here are intended to support future food-web studies applying stable isotope mixing models to quantify carbon sources in the polar marine environment.